Understanding the effect of tire pressure and speed on vibrations transmission to the handlebar in road cycling - Sanseverino, G.; Schwanitz, S.; Krumm, D.; Odenwald, S. (spinfortec2020digital: 13. Symposium der dvs-Sektion "Sportinformatik und Sporttechnologie" vom 24.-25. September 2020 in Bayreuth, 2020)
The aim of this research was to understand how tire pressure and speed affect vibration transmission to the handlebar of a road bicycle. Data acquired in field tests were processed using Analysis of Variance (ANOVA). This research shows that both increasing speed and tire pressure increased VDV and thus vibrations transferred to the handlebar. In any case the effect of speed on VDV was much more significant than the one of tire pressure and this is in line with ANOVA results.